Chemical constituents of the twigs of Mangifera Indica (Mangga Telor) / Hasbarinda Binti Hasan - Hasan, Hasbarinda (Faculty of Applied Sciences, 2008)
a study of the chemical constituents of Mangifera indica twigs was conducted. The dried powder of twigs was extracted with methanol. The isolation of the compounds was achieved by chromatographic techniques. Structure determinations were done using 1 H NMR, 13 CNMR, and DEPT. From the twigs of Mangifera indica , 4, 8Bishydroxymethyl7( 1hydroxy1methylethyl)1(3,4,6trihydroxy5hydroxymethyltetrahydropyran2yl) 478trihydronaphthalen2onewere isolated.